PERENCANAAN PENDIDIKAN DAN PENGEMBANGAN IPTEK - Sukarsono, Tono (Jurnal Bestari, 1991)
Ther is a special Interdependence between man and technology as the product of his mind and engineering. The Hardest mind's survival and struggle, the Excellent technology he produces. In other words, the education is the base of scientific and technoligical products of his long life struggle. Science and technology, therefore, should be grown up from estabilished education. the best curriculum, methodology and other educational framework, however, cannot be applied without the main principle: ethic.